(untitled) (International Current Pharmaceutical Journal, 2016)
In this study, the effect of the incubation time, incubation temperature, pH, metal and sodium ions on the antibacterial activity of chitosan against food borne spoilage bacteria focused. Aeromonas hydrophila and Staphylococcus aureus were used as two food borne bacteria. Acetic acid was used dissolving of chitosan. Results showed that chitosan solution at 5 mg/mL significantly inhibited the growth of A. hydrophila and S. aureus in presence of time, pH and metal ions (p <0.01). However, temperature did not significantly affect the antibacterial activity (4°C, 25°C and 37°C) (p >0.01). Chitosan activity increased with increasing incubation time. The influence of below pH 6 on the antibacterial activity of chitosan was significantly influenced (p<0.01). The addition of Ba+2 reduced chitosan activity against A. hydrophila while the addition of Ca+2 have increased chitosan activity against S. aureus. Sodium ions at a concentration of 25 mM reduced chitosan activity against S. aureus. These results show that chitosan can be used food industry to prevent the development of spoilage bacteria. Erdem et al., International Current Pharmaceutical Journal, April 2016, 5(5): 45-48